Harnessing the T Cell to Treat Multiple Myeloma: Dawn of a New Therapeutic Paradigm - Keller, Alana L.; Sherbenou, Daniel W.; Forsberg, Peter A.; Mark, Tomer M. (Frontiers in Oncology, 2022)
Multiple myeloma is an incurable hematologic malignancy. The typical disease course for myeloma patients is characterized by initial response to treatment followed by eventual development of resistance. Subsequent cycles of remission and relapse proceed as long as patients have new lines of therapy available to them, terminating in eventual death. This reality has prompted development of many novel immunotherapeutics. Many of these drugs exploit the cytotoxic capabilities of the patients’ own T cells, effectively redirecting them to myeloma cells that are otherwise evading immune attack. Approaches including CAR T cell therapy and bispecific antibodies have displayed impressive efficacy in clinical trials for myeloma patients. This review examines the origin of T cell utility in multiple myeloma therapy and investigates the benefits and risks of these exciting new treatment strategies.